Trends and type of ethical reasoning between managers of the public and private sectors of Puerto Rico, Colombia and Costa Rica - Vera Rodríguez, Hernán A. (2018)
A mixed methodology study, with a quantitative emphasis is presented. Its main purpose was to identify the way in which managers would act in hypothetical situations related to bribery, coercion, cheating, theft, discrimination and transparency. The sample consisted of 281 managers from public and private organizations in Puerto Rico, Colombia and Costa Rica. Data and information gathering was performed using the Spanish version of the Ethical Situations Questionnaire developed by Fritzsche and Oz (2007). Descriptive statistical analyzes, t-tests for independent samples and one way Anova’s were used for the analysis of quantitative data. On the other hand, content analysis in which the qualitative responses were grouped by categories was used to analyze qualitative information. Results show, that in most cases, sampled managers would take an ethical decision in an ethically ambiguous scenario. Results showed significant statistical differences between the ethical tendencies of public and private sector managers in some of the ethical situations. In general terms, slightly stronger ethical trends were observed among public sector managers. On the contrary, the study did not find statistically significant differences due to the country in which they worked. Finally, the axiological reasoning was the type of reasoning mostly used by surveyed managers, when faced with an ethically ambiguous dilemma or situation.